2016
DOI: 10.1007/s11701-016-0590-z
|View full text |Cite
|
Sign up to set email alerts
|

Da Vinci robot emergency undocking protocol

Abstract: The role of robot-assisted surgery across gynaecology is evolving with increasing numbers of procedures being undertaken with varying degrees of complexity. While the risk of conversion is low at approximately 1 %, the reasons for conversion are variable. These range from technical issues with the robot, surgical complications such as haemorrhage and anaesthetics issues such as an inability to ventilate the patient adequately. While many conversions to open or laparoscopic approach are not due to life-threaten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…In a situation in which emergency undocking is performed, the coordination of the entire interprofessional team involved in the operating room is required. There is a paucity of literature available outlining protocols or training for this procedure [4]. A team generally consists of a circulating nurse, scrub nurse, anesthesiologist, bedside assist surgeon, and robot console surgeon.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a situation in which emergency undocking is performed, the coordination of the entire interprofessional team involved in the operating room is required. There is a paucity of literature available outlining protocols or training for this procedure [4]. A team generally consists of a circulating nurse, scrub nurse, anesthesiologist, bedside assist surgeon, and robot console surgeon.…”
Section: Introductionmentioning
confidence: 99%
“…Limited access to the patient can delay the start of effective measures to treat a life-threatening emergency and, in some cases, has resulted in fatality [3,11]. It is well-established that clear, concise communication is paramount during surgical emergencies for the benefit of patients and operating room staff [4,12-13]. The need for a protocol has been well-described in the robotics field since many practicing robotic surgeons have not encountered this situation in their training.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulating this situation and having an emergency plan can improve the time of preparation and intervention. O'Sullivan et al [60] experienced a respiratory complication during a robotic sacrocolpopexy. The patient had a decreased sPO 2 and increased airway pressure, thus an emergency undocking of the robotic arms was required.…”
Section: Emergency Situationsmentioning
confidence: 99%
“…The patient had a decreased sPO 2 and increased airway pressure, thus an emergency undocking of the robotic arms was required. After this complication they reported that they created an emergency undocking protocol, which indicates the roles of each member of the crew in emergency situations [60] . Also Huser et al [61] reported that proper training with repeating simulations improved the time for resuscitation in simulations.…”
Section: Emergency Situationsmentioning
confidence: 99%